The efficacy of endoscopic ultrasonography in local staging of rectal tumors - Belkıs Ünsal; Emrah Alper; Behlül BAYDAR; Mahmut Arabul; Fatih Aslan; Mustafa Çelik; Zafer BUYRAÇ; Serdar AKÇA (Turkish Journal of Gastroenterology, 2019)
-